Strategy of Drum Band Extracurricular Activities to Improve Children's Musical Intelligence - M Musrifah; Junita Dwi Wardhani (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the strategies used in implementing drum band extracurricular activities as an effort to enhance children’s musical intelligence, particularly their ability to recognize musical elements such as rhythm, pitch, melody, and timbre.Method: The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation during drum band practice sessions. Research informants included drum band coaches, accompanying teachers, and parents, while the subjects were Class B children at TK Aisyiyah Bustanul Athfal XI Saren.The results showed that children participating in drum band extracurricular activities experienced significant improvement in understanding basic musical concepts such as rhythm, pitch, melody, and timbre. In contrast, children who did not participate demonstrated relatively lower musical abilities.Application/Originality/Value: The findings can serve as a reference for drum band coaches and teachers in developing musical intelligence through structured teaching methods, such as training correct stick-handling techniques and using a metronome to help children adjust their playing to a set tempo. Additionally, the selection process conducted by coaches and accompanying teachers ensures each child is placed according to their talent and abilities. This study highlights the important role of extracurricular activities in supporting the development of musical abilities in early childhood.